DYNAMIC PERFORMANCE ANALISYS OF ROAD COMBINED VEHICLE FOR SUGAR CANE TRANSPORTATION - Horta Gutiérrez, Juan Carlos; Carlos Canale, Antônio (Centro Azúcar Journal, 2008)
Analysis of the dynamic behaviour of road combined vehicles for sugar cane transportation. The study is about the directional stability of the type commercial combined truck semi-trailer as a function of load, of moment of inertia and of the position of the centre of gravity of set semi-trailer - load. The curves are obtained that represent the characteristic movements and the ratio of damping for these movements during curved and straight trajectories, showing the mains variations of dynamic characteristics with these variables. An articulated vehicle is modelling with acceptance of several simplifications and hypothesis, analysing a performance of vehicle and observing significant variations on dynamic response. Results show the necessity of that the users take a maximum care in relation with load conditions due to their high variability and their great influence on safety and use of these type road vehicles.